The Role of Early Warning Systems in Reducing Disaster Impacts: An Analysis of Digital Infrastructure Readiness - Parlia Romadiana; Wishnu Aribowo Probonegoro; Lili Indah Sari (Oikonomia : Journal of Management Economics and Accounting, 2025)
The increasing intensity and frequency of natural disasters require disaster risk reduction systems that are not solely technology-driven but are also supported by adequate digital infrastructure readiness and governance. Early Warning Systems (EWS) are widely recognized as strategic instruments for reducing disaster impacts; however, their effectiveness remains inconsistent across regions. This study aims to analyze the role of Early Warning Systems in reducing disaster impacts by emphasizing digital infrastructure readiness as a key determinant of system effectiveness. The study employs a qualitative descriptive-analytical method with a policy and system analysis approach, using secondary data from reputable scientific literature, national and international policy documents, and disaster management reports. The findings indicate that EWS often function only as information delivery mechanisms due to limitations in digital infrastructure, fragmented governance, and low levels of community digital literacy. The readiness of communication networks, data system integration, energy reliability, and institutional coordination are identified as critical prerequisites for transforming EWS into effective collective mitigation mechanisms. This study concludes that strengthening EWS requires a systemic approach that integrates technology, digital infrastructure, and disaster governance to achieve meaningful disaster impact reduction.